Relationship Of Industrial Practice Results With Students 'Work Interest In Smk Negeri 3 Solok City - Suka Yana; Asmar Yulastri (Universitas Negeri Padang, 2021)
This study aims to describe work interest, the relationship between the results of industrial work practices with student work interests, and the results of industrial work practices. This type of research is descriptive quantitative correlational. The students of SMK Negeri 3 Solok City who became the population of this study used a sample of 59 people taken by proportional random sampling technique. Students who have had industrial work practices become the source of data in this research. The distribution of survey questionnaires is a collection of data using a Likert scale that has been tested for validity and reliability. In this study, the method of descriptive analysis and data categorization was carried out based on the ideal score of data analysis techniques. In addition, the data analysis requirements test, correlation coefficient analysis, and correlation significance coefficient analysis were carried out. The results of this study are the overall industrial work practices are in the right category, general interest in work is in the very high category, and there is a positive and significant relationship between the two. This study concludes that the results of industrial work practices affect student work interest.